Deception Aversion - Béla Elmshauser; Evan Friedman; Yoon Joo Jo (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Conveying private information to interested parties is central to almost every economic and social activity. In such interactions, the sender may lie by misreporting the truth, but may also deceive by inducing inaccurate beliefs about the payoff-relevant state. While a huge experimental literature documents aversion to lying, there is little evidence regarding aversion to deceiving others. Deception aversion is conceptually difficult to document because it depends on unobserved second-order beliefs: the sender's belief over the receiver's belief (over the payoff-relevant state). In this paper, we introduce a novel game and show theoretically how to identify deception aversion from choice data alone, with minimal assumptions on second-order beliefs. We run a laboratory experiment and find strong support for deception aversion that is robust to several natural variations of the game. Many subjects lie in order to avoid deception, and structural estimates imply that 30% of subjects are deception-averse.
Keywords: C44; C72; C92; 330; lying; deception; lying aversion; deception aversion; image concerns; strategic communication; psychological game theory